Applying Combined Langmuir–Freundlich Model to the Multi-Component Adsorption of BTEX and Phenol on Smectite Clay - Marilda N. Carvalho; Cesar A.M. de Abreu; Mohand Benachour; Deivson C. S. Sales; Osmar S. Baraúna; Mauricio A. da Motta Sobrinho (Adsorption Science & Technology)
Adsorption using clay is increasingly being applied in the secondary treatment of effluents contaminated with organic compounds discharged from oil industries. This study was aimed at applying a combined Langmuir–Freundlich model to describe the multi-component adsorption of organic compounds such as benzene, toluene, ethylbenzene, xylenes and phenol using smectite clay. The results of the study well fitted with the model developed. In addition, the model parameters suggest that maximum adsorption capacities (q m ) can be achieved between 2.45 (toluene) and 22.40 mg g −1 (phenol). The equilibrium points for the compounds were achieved in approximately 20–30 minutes.